menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
6-7(x+1)= -3(2-x) How do you solve this?
asked
Jan 4, 2022
53.8k
views
0
votes
6-7(x+1)= -3(2-x)
How do you solve this?
Mathematics
high-school
Diffeomorphism
asked
by
Diffeomorphism
5.2k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
6
votes
Step-by-step explanation
Given the equation.
Distribute/Simplify
Solve the equation for x-term by making x as the subject.
Answer Check by substituting the value of x in the equation.
The equation is true for x = 1/2.
Answer
Harshay Buradkar
answered
Jan 9, 2022
by
Harshay Buradkar
6.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.6m
answers
Other Questions
Solve for y in terms of x. 2/3y - 4 = x y = x + 6 y = -x + 4 y = -x + 6 y = x + 4
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org